Recommendations for Implementing Gamification for Mental Health and Wellbeing - Cheng, Vanessa Wan Sze (Frontiers in Psychology, 2020)
Gamification is increasingly being proposed as a strategy to increase engagement for mental health and wellbeing technologies. However, its implementation has been criticised as atheoretical, particularly in relation to behaviour change theory and game studies theories. Definitions of the term “gamification” vary, sometimes widely, between and within academic fields and the effectiveness of gamification is yet to be empirically established. Despite this, enthusiasm for developing gamified mental health technologies, such as interventions, continues to grow. There is a need to examine how best to implement gamification in mental health and wellbeing technologies in a way that takes quick production cycles into account while still emphasising empirical investigation and building a rigorous evidence base. With reference to game studies and the medical (eHealth/mHealth) literature, this article interrogates gamification for mental health and wellbeing by examining core properties of the game form. It then explores how gamification can best be conceptualised and implemented for mental health and wellbeing goals from conceptualisation through to iterative co-development and evaluation that accommodates software development schedules. Finally, it summarises its conceptual analysis into recommendations for researchers and designers looking to do so. These recommendations are: 1) Assess suitability, 2) Implement to support, 3) Assess acceptability, 4) Evaluate impact, and 5) Document comprehensively. These recommendations aim to encourage clear language, unified terminology, the application and evaluation of theory, comprehensive and constant documentation, and transparent evaluation of outcomes.